2012
DOI: 10.1186/1471-2369-13-21
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaglomerular apparatus hyperplasia under dual angiotensin blockade. A footprint of adequate RAS inhibition or a concern for renal fibrosis?

Abstract: BackgroundDual renin-angiotensin system blockade with angiotensin-converting enzyme inhibitors and angiotensin receptor blockers has been advocated to minimize proteinuria. However, recent trials have questioned the renal safety of this approach. Our understanding on the molecular effects of dual blockade in humans is incomplete.Case presentationWe present a patient with corticoid resistant nephrotic syndrome who developed marked juxtaglomerular apparatus hyperplasia and renin expression in the context of dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In this study, we also found that the long-term inhibition of the RAS induced arteriolar hypertrophy in humans. Some case reports showed hypertrophy of the JG area in patients with hypertension treated with RASi ( 35 ). In a recent study of the kidneys from hypertensive patients treated with antihypertensive agents, arteriolar hypertrophy was observed in patients with RASi and not detected in patients without RASi ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that the long-term inhibition of the RAS induced arteriolar hypertrophy in humans. Some case reports showed hypertrophy of the JG area in patients with hypertension treated with RASi ( 35 ). In a recent study of the kidneys from hypertensive patients treated with antihypertensive agents, arteriolar hypertrophy was observed in patients with RASi and not detected in patients without RASi ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown better effects for ACE inhibition over AT 1 antagonism on renal protections in diabetic patients who have features of chronic kidney disease (Baltatzi, Savopoulos, & Hatzitolios, 2011; Hsu et al, 2017; Laverman et al, 2004; Mavridis, Palmer, & Strippoli, 2016; Wu et al, 2017). In some studies, AT 1 antagonist treatment is not protective for glomerular health (Fernandez‐Fernandez et al, 2012; Nagai et al, 2020; Nakanishi et al, 2011). The discrepancies between these trials could be due to differences in experimental design and medicine used.…”
Section: Discussionmentioning
confidence: 99%